Empowerment of Tourism Awareness Groups Through Administration and Tourism Management Training in Lebih Village, Gianyar - Dewi, I Gusti Agung Ayu Yuliartika; Yudhiantara, I Made; Andriastuti, Komang Tri Putri (Abdi Masyarakat, 2025)
This community service program was carried out to empower the Tourism Awareness Group (Pokdarwis) of Lebih Village, Gianyar, through training in administration and tourism management. The background of this activity lies in the low administrative and management capacity of local tourism resources, which has hindered optimal destination management. The program aimed to enhance the skills of Pokdarwis members and administrators in organizational administration, program planning, and utilization of tourism potential. The implementation methods included preliminary observation, module preparation, face-to-face training, group discussions, and technical assistance. The results showed an improvement in participants’ understanding of organizational administration, financial recording, and promotion strategies based on local potential. Evaluation was conducted through questionnaires and practical assessments, indicating that most participants were able to apply the trained skills. The program’s outputs included training modules, standardized administrative formats, and an annual work plan for the Pokdarwis. In conclusion, the training effectively improved Pokdarwis’ capacity towards more professional and sustainable tourism management.